Destruction of giant cluster-like vesicles by an ultrasonically activated device. (24th June 2016) - Yahagi, Ryosuke; Yoshida, Kenji; Zhang, Yiting; Ebata, Masahiko; Toyota, Taro; Yamaguchi, Tadashi; Hayashi, Hideki
Abstract: In this paper, we propose a technically simple method of destroying a tissue marker composed of giant cluster-like vesicles (GCVs) to facilitate laparoscopic surgeries; the method releases various biological tracers contained in GCVs. An ultrasonically activated device (USAD) emitting 55.5 kHz ultrasound was employed for this purpose. Optical microscopy and fluorospectrophotometry revealed the destruction of GCVs after ultrasound irradiation when the blade tip was set 1.0 mm or closer to, but not directly in contact with, a GCV-containing cell. This means that USAD could be safely used for destroying this GCV tissue marker in clinical settings.